Overwhelmed: Accountability and work intensification in the neo-liberal university. The case of Chile - Vicente Sisto (Arizona State University, 2020)
In a context of university policies guided by neo-liberal models, the University has been strongly challenged by the increase in accountability and performance-based financing mechanisms. These policies challenge the work of the University and its workers: academics. This study explores, from the position of academics, how the accountability policies implemented from the central level are deployed in the local space, challenging academic work and its workers. A total of 36 interviews were analyzed. Findings showed that certain themes emerged as the most relevant concerning daily work. Among these, curricular assessment systems acquire a leading role in establishing which actions count and which do not. The interviews also allowed an understanding of how participants experience these policies. The intensification of work emerges as the most relevant process accounting for a work that goes beyond its limits occupying personal, family, rest, and social spaces. This also occurs within a context of an increasing questioning of the meanings and values of academic work that are being installed by university policies of high accountability.